Editor's Choice – Two Year Results of the Randomised DISCOVER Trial Comparing Covered Versus Bare Metal Stents in the Common Iliac Artery. (March 2023) - Bekken, Joost A.; Vroegindeweij, Dammis; Vos, Jan Albert; de Vries, Jean-Paul P.M.; Lardenoije, Jan Willem H.P.; Petri, Bart-Jeroen; Pierie, Maurice E.N.; van Weel, Vincent; Teijink, Joep A.W.; Fioole, Bram
Abstract : Objective: It has been suggested that covered stents (CS) may lower restenosis rates compared with bare metal stents (BMS) after endovascular treatment of the common iliac artery. This trial aimed to provide additional evidence on the efficacy of CS vs. BMS in the common iliac artery. Methods: This multicentre, randomised, single blind controlled superiority trial compared balloon expandable CS and balloon expandable BMS for advanced atherosclerotic lesions in the common iliac artery; this was defined as a stenosis > 3 cm in length or occlusion. The primary end point was freedom from binary restenosis after two years of follow up. The study was conducted according to the principles of the Declaration of Helsinki (version: October 2008) and registered with the Dutch Trial register (NTR3381). Results: One hundred and seventy-four limbs were included between 2012 and 2019 with 87 limbs in each group. Six patients crossed over from the BMS group to the CS group but were analysed according to an intention to treat principle. Freedom from binary restenosis after two years of follow up was 84.7% (95% CI 76.7 – 92.7%) in the BMS group and 89.1% (95% CI 82.4 – 95.8%) in the CS group ( p = .40). Freedom from occlusion was 95.0% (95% CI 90.3 – 95.7%) in the BMS group and 96.4% (95% CI 92.5 – 100%) in the CS group ( p = .66). Freedom from target lesion revascularisation was 91.1% (95% CI 84.8 – 97.3%) and 95.2% (95% CI 90.7 –99.7%), respectively ( p = .31). Technical success, complications, haemodynamic success, and clinical success were also comparable between both groups. Per-protocol analysis did not affect the outcomes of the study. Conclusion: No difference was found between balloon expandable CS and BMS for treating advanced atherosclerotic lesions of the common iliac artery.